Application of log-periodic power law to oil spot market - Virtanen, Lauri (2025)
Oil price crashes and bubble regimes in oil spot markets have a substantial impact on the real economy. One model that has been proposed for detecting bubble regimes and forecasting the most probable date of the crash is the log-periodic power law. The model aims to detect log-periodic oscillations in price data which reveal a bubble regime and enable the model to forecast the most probable crash date.